Aspecte ale calității vieții de familie și devianța copiilor - Fleșner, Margareta (Calitatea Vieții, 1992)
A child’s behaviour is undoubtedly shaped by the way of his family’s life within it he is socialized. As the family environment has of a lot of deficiencies (afective, moral and educational ones), the child’s behaviour becomes often deviant in comparison with the social rules and valués.